Analysis of Paratransit Feeder-Service Pilot: Projected versus Actual Ridership and Cost-Benefit Results. Issue 8 (December 2018) - Hansen, Todd
The research presented examines projected and actual operational cost savings from the implementation of a paratransit feeder-service pilot in Houston, Texas. Transit agencies can offer feeder service by utilizing demand–response paratransit vehicles to connect to fixed-route rail and buses for the remaining portion of the trip. Feeder service has the potential to create savings in operating costs for transit agencies along with additional travel options for ambulatory paratransit customers. At the direction of Houston METRO, researchers projected the number of trips that would transfer to feeder service from standard paratransit service to support the agency in designing a pilot. Subsequently, the researchers analyzed the actual feeder-service trip data at the conclusion of the pilot period to assist the agency in studying the final pilot results. The presented research compares projected trip-demand and operational costs conducted before the pilot period to actual trip and cost savings during the 6-month pilot to determine the rate of trip transfer between regular paratransit service and combination feeder-service connecting paratransit to fixed-route service. The research analyzes the cost per revenue hour for feeder-service trips compared with the pre-pilot projections and the actual cost of the same trip using entirely paratransit service to show the net benefit for the transit agency. The results show lower operational costs for paratransit feeder-service compared with regular paratransit service during the pilot period. Transit agencies interested in implementing feeder service can use the research methodology to estimate the impacts of potential paratransit feeder trips.